Meanings and practices of customer experience managment. - Arkadan, Farah (Cranfield University, 2017)
The notion of creating a superior customer experience is increasingly determining business focus and shaping marketing practice. The strategic role of customer experience management (CEM) is evidenced in the central role customer experience has in mission statements of prominent companies and the addition of customer-dedicated teams and senior-ranking roles. The use of the term “experience” both signifies and imposes a shift in marketing management thinking and practice because an experience, unlike a product or service, by definition, is always from the point of view of the person doing the ‘experiencing’ (e.g. the customer). Despite its prominence and popularity in practice, it is unclear what customer experience management (CEM) as an overall business focus means or entails. This research comprises a doctoral thesis presented in ‘paper format’, presenting the work in the form of four papers in journal paper style rather than in the style of a monograph. The research is conducted in three phases ((1) a systematic literature review of the field, (2) longitudinal multi-informant case studies and (3) new multidimensional scale development) with the aim of answering the overall research question of, what are the meanings and practices of customer experience management? The thesis contributes to CEM literature and theory and provides several contributions to practice. Key contributions of this research are (1) systematically identifying a comprehensive and integrative body of CEM literature, (2) developing a grounded-theory firm-side conceptualization of CEM practice and organizational values, (3) demarcating CEM from market orientation (i.e. a prevalent firm-wide marketing management approach) and proposing an updated and distinctive orientation relabelled customer experience orientation (CXO) and (4) developing a scale for measuring CEM organizational values and exploring their associations with performance outcomes. The thesis concludes with a discussion of limitations and directions for future research.
Keywords: Customer experience management; practice theory; customer experience orientation; organizational culture; systematic literature review; measurement scale; performance outcomes